Umbilical Artery Cord Gas Abnormalities in the Presence of a Nuchal Cord in Term Singleton Pregnancies: A Cohort Study - Zahedi-Spung, Leilah Deborah; Raghuraman, Nandini; Carter, Ebony B.; Cahill, Alison G.; Rosenbloom, Joshua I. (American Journal of Perinatology, 2022)
Objective The clinical significance of nuchal cord (NC) at the time of delivery is unclear. Studies have found that NC is associated with lower umbilical artery (UA) pH. Since fetal hypercarbia precedes respiratory acidosis, we hypothesize UA pCO2 is elevated in neonates with NC at the time of delivery.Study design This is a secondary analysis of a prospective cohort study of women with full-term singleton pregnancies admitted in labor or for induction of labor at an institution with a universal umbilical cord gas policy. We compared patients with NC at the time of delivery to those without NC. Women were excluded if they did not have validated UA gases, had a major fetal anomaly, or had an intrauterine fetal demise. The primary outcome of the study was UA pCO2. Secondary outcomes were other components of UA gas and neonatal morbidity composite. Baseline characteristics were compared utilizing chi-square or Fisher's exact test or the Student's t-test. UA gas parameters were compared using the Kruskal–Wallis test. Multivariable logistic regression was utilized to adjust for confounders.Results Of the 8,580 study participants, 7,608 had validated umbilical cord gases. The incidence of NC in the population was 24.15% (n = 1,837). UA pCO2 was higher in those with NC than without (58 mm Hg [53–64] vs. 55 mm Hg [50–60], p < 0.01). There was a greater odds of hypercarbia in the NC group (pCO2 > 65 mmHg; adjusted odds ratio [aOR]: 1.97, 95% confidence interval [CI]: 1.72–2.25, p < 0.01). Additionally, the NC group was more likely to be mildly acidemic (pH < 7.2, aOR: 1.74, 95% CI: 1.51–2.01, p < 0.01). There was no difference in composite neonatal morbidity between the groups.Conclusion NC is associated with an increased risk of hypercarbia and acidemia. However, this is not associated with increased risk of neonatal morbidity.Key Points
Keywords: acidemia; hypercarbia; neonatal morbidity; nuchal cord